The administrative regulatory process - Heffron, Florence A.; McFeeley, Neil (New York : Longman House, 1983)
This book is addressed to both of their concerns and attempts to provide an overview of the political and legal aspects of the regulatory process, the controversies surrounding it and the major reform proposals that have been suggested to improve it.
Part I. The constitutional, legal and political framework or administrative power -- Part II. Basic administrative processes -- Part III. Judicial controls -- Part IV. Regulation: consequences and reforms.
Includes index.
Keywords: ADMINISTRATIVE LAW -- UNITED STATES